Sistema eleitoral brasileiro: um compêndio de sua gênese, evolução e características - Vilas Boas, Suellen Tanys (2016)
In this study aims to approach the details of the various structural changes and government occurred in Brazil, from the Independence Day until nowadays, emphasizing and highlighting the intrinsic aspects of the democratic electoral system. The objective of the study was to formulate a theoretical reflection on the Brazilian electoral system, highlighting political, social and regulatory aspects that have marked its construction process. Therefore, it was conducted a bibliographic study on integrative historical perspective with theoretical reflections arising from the political theory and public administration. The literature review was structured as follows. First, it will be to analyze the thinking of some philosophers and political scientists on the State and government in order to introduce the prominent word of this work - democracy. In the following chapters it will stick closely to Democratic Theory, passing by antiquity to the modern age, at the end of the chapter will be given a special focus on its representative aspect, considering this is the focus of the study. After understanding the idiosyncrasies of the State, government and democracy it is necessary to enter in the discussion related to the research problem, which is: How the Brazilian electoral system was structured after the Independence Day? For this, Brazilian electoral political history was didactically subdivided into six stages, they are: 1) Brazil Empire (1822 - 1889); 2) Old Republic (1889 - 1930); 3) Era Vargas (1930 -1945); 4) Redemocratization of Brazil (1946 -1964); 5) Military Dictatorship (1964 -1985) and; 6) New Republic: Contemporary Brazil. It is glimpsed to the end that the country was living in a democratic routine in which authoritarian amazements of Era Vargas and the Military Dictatorship, for example, were in the past, however, modern democracy still faces political obstacles of that time combined other problems with the current feature such with: crisis in political representation and popular alienation. The study also showed the need to build the country a real popular democratic authenticity - social emancipation - because only from this, the electoral history can be reformulated and active in the democratic sense.